Structure of Turbulent Flow in a Rod Bundle - Don, Armel (Université d'Ottawa / University of Ottawa, 2016)
The structure of turbulence in the subchannels of a large-scale 60 degree section of a CANDU 37-rod bundle was studied at Reynolds numbers equal to 50,000, 100,000 and 130,000. Measurements were conducted at roughly 33.81 rod diameters from the inlet of the rod bundle using single-point, two-component hot-wire anemometry. Analysis of the axial velocity signal indicated a weak effect of Reynolds number on the axial velocity distribution and a bulging of axial velocity contours toward the narrow gaps. The normalised normal Reynolds stresses and the normalised turbulent kinetic energy were found to decrease as the Reynolds number increased. The radial Reynolds shear stress varied linearly with radial distance from the rod, crossing zero at the location of local maximum of the axial velocity. This stress was symmetric about the central rod whereas the azimuthal Reynolds shear stress was anti-symmetric. The Reynolds number effect was weak but measurable on the integral length scales of the axial and radial velocity fluctuations but negligible on the integral length scale of the azimuthal velocity fluctuations, especially in the gap regions. The Taylor and Kolmogorov microscales increased from the wall toward the centre of the subchannel and decreased as the Reynolds number increased. The wall shear stress stress distribution around the central rod indicated no effect of Reynolds number, when normalized by the corresponding average. The wall shear stress reached local minima at rod-wall and rod-rod gaps and local maxima in the open flow regions. Vortex streets were generated within the subchannels very close to the inlet of the rod bundle. The convection speed and frequency of the vortex street were found to increase proportionately to Reynolds number, whereas the vortex spacing was not affected by the Reynolds number.
Keywords: CANDU; coherent vortices; thermalhydraulics; rod bundle; vortex street; subchannel